Concept of “Subjects of Person’s Detention without Investigating Judge’s Ruling” - Manyk , O. V.; Маник, О. В. (Legal, Economic Science and Praxis. - 2022. - № 7. - P. 13-16, 2022)
Автор здійснив аналіз наукових підходів до тлумачення термінів «суб’єкт», «суб’єкт права», «суб’єкт правовідносин». Під суб’єктами затримання особи без ухвали слідчого судді запропоновано розуміти сукупність осіб, які відповідно до приписів чинного національного законодавства в межах суспільних відносин щодо затримання особи без ухвали слідчого судді, наділяються процесуальними правами та обов'язками чи повноваженнями.

The author of the article has emphasized that exercising the detention of a person without the investigating judge's ruling is related to the emergence, further development, modification and termination of the relevant social relations with their characteristic corpus delicti. It has been noted that the functioning of such social relations takes place considering their regulatory legal regulation, where it is quite common to designate them as legal relations. The author has accomplished the analysis of scientific approaches to the interpretation of the terms of “subject”, “subject of law”, “subject of legal relations”. It has been suggested to understand the subjects of a person's detention without the investigating judge's ruling as a set of persons who, in accordance with the prescriptions of the current national legislation, within the limits of social relations regarding the detention of a person without the investigating judge's ruling, are granted procedural rights and duties or powers. Given the specifics of the emergence and development of social relations during the detention of a person without the investigating judge's ruling, its functioning as one of their main subjects in the whole, has been offered to be considered as the person who is detained without the investigating judge's ruling. The very person is endowed with the appropriate procedural status within the given social relations, as a result of which he / she has procedural rights and obligations, guarantees of their implementation. This subject is considered as one of the main ones, because such social relations cannot arise and exist in the future without the existence of such a subject. It has been emphasized that persons authorized by the current national legislation to exercise such detention should be considered as the leading subjects of a person's detention without the investigating judge's ruling. As a separate group of subjects of a person's detention without the investigating judge's ruling, the author has singled out the subjects of ensuring the rule of law. Subjects of control and supervisory activities have been named within this group.

Дан анализ научных подходов к толкованию терминов «субъект», «субъект права», «субъект правоотношений». Предложено понимать под субъектами задержания лица без постановления следственного судьи как совокупность лиц, которые в соответствии с предписаниями действующего национального законодательства в пределах общественных отношений по поводу задержание лица без постановления следственного судьи, наделены процессуальными правами и обязанностями или полномочиями.
Keywords: затримання особи без ухвали слідчого судді; суб'єкти затримання; уповноважена службова особа; затримана особа; суб’єкти забезпечення верховенства права; кримінальне провадження; кримінально-процесуальні відносини; detention of a person without investigating judge's ruling; subjects of detention; authorized official; detained person; subjects of ensuring rule of law; criminal proceedings; criminal procedural relations; задержание лица без постановления следственного судьи; субъекты задержания; уполномоченное должностное лицо; задержанный человек; субъекты обеспечения законности; уголовное судопроизводство; уголовно-процессуальные отношения